Evaluation of prognostic factors and survival of patients with metastatic bone disease - Abumarzouq, Mahmoud F. R. (2016)
INTRODUCTION Management of metastatic bone disease is still challenging, along with the improvement in managing primary solid tumors, patients survive longer and they become potential to have metastatic lesions of bone more than they had before. A variety of treatment options could possibly be given to those patients includes medical treatment, radiation, chemotherapy and surgical intervention. The surgical intervention for metastatic bone lesions gives satisfactory outcome. However, there are few factors affecting the survival of patients with metastatic bone disease such as performance status, type of primary tumor, neurology deficit, pathologic fracture, visceral organ metastasis and chemotherapy administration. This study was conducted to evaluate the prognostic factors affecting the median survival and patient’s quality of life. METHODS A total of 40 patients with metastatic bone disease treated surgically between 2008 to 2015 at orthopedics oncology unit, Hospital Universiti Sains Malaysia were evaluated retrospectively, for survival prognostic factors, while the performance status questionnaire of ECOG (Eastern Cooperative Oncology Group) was used to assess the patient’s quality of life at three, six and twelve month after the surgery. Subsequently, survival rate was analyzed by the Kaplan-Meier method. RESULTS There were 29 female and 11 male, the most common primary tumor was breast cancer with 42.5%, followed by thyroid cancer 17.5%. Over all 14 (37.8%) patients survived, while 23(62.16%) patients died, and the median survival was 36 months. Mean age at presentation was 54.43 years, and there were 30% (12/40) above 60 years and 70% (28/40) below 60 years. Based on the age groups, the survival rate was statistically significant p value (0.028). Other prognostic factors include chemotherapy administration and site of bone metastasis (appendicular, axial bone or both together) were also significantly correlated with the survival p value of (0.003, 0.021), respectively. Types of the surgery was a significant factor associated with the survival (p-value 0.038), resection and endoprosthesis surgery was the most procedure performed in our center for (hip, proximal femur, shoulder and around knee joint lesions) 58.97% (n=24), followed by Harrington procedure for pelvic involvement which was 17.95% . Performance status ECG (0-2) and ECOG (3-5) of patients was evaluated and found to be statistically significant as a prognostic factor for survival. CONCLUSION In conclusion, the prognostic factors that significantly affect the survival of patient with bone metastasis were age which was less than 60, location of bone lesions, previous chemotherapy, and the type of performed surgical procedure. Additionally, the study revealed that the quality of life significantly correlated with the types of surgery and overall survival. Furthermore, the performance status (ECOG) significantly correlated with the types of surgery and age.